Primary Mucinous Carcinoid of the Ovary Arising in a Mature Cystic Teratoma: A Case Report with Review of the Literature - Huang, MD, PhD, Ying; Kumarapeli, MD, PhD, Asangi; Chen, MD, PhD, Frank; Paczos, MD, Tamera (North American Journal of Medicine and Science, 2012)
Primary mucinous carcinoid of the ovary is an extremely rare neoplasm with less than thirty cases reported in the English literature. The clinical behavior and pathologic features have not been well characterized. Here we report a case of a 42-year-old female who underwent laparoscopic salpingo-oophorectomy for a left ovarian mass. The ovary was received for histopathologic evaluation in multiple pieces among which a 1.1 cm firm tan nodule was identified. Histologically, this nodule composed of small glandular structures scattered in pools of mucin adjacent to a mature cystic teratoma. The glands were lined by goblet and columnar cells and showed no appreciable atypia. Immunohistochemistry revealed intense, diffuse staining pattern of the mucinous tumor component for CK20, CDX-2 and villin and focal patchy positivity for CK7 and chromogranin. Metastatic tumors from the GI tract and Krukenberg tumors were considered in this patient’s differential diagnosis. She subsequently underwent a total abdominal hysterectomy with staging and appendectomy. However, no evidence of primary gastrointestinal malignancy or residual ovarian disease was found. The histologic and immunohistochemical characteristics of the tumor, its intimate association with a mature cystic teratoma and the absence of primary malignancy elsewhere are compatible with the diagnosis of a primary ovarian mucinous carcinoid tumor. This case is presented to raise the awareness of a rare tumor entity among the pathology and gynecologic communities.